Economics of agricultural production and resource use - Heady, Earl Orel (New York, Prentice-Hall, 1952)
The book provides a skeleton of basic principles upon which problems in agricultural production and resource can be analyzed.
includes index
occ 17/01/2019
Loans
Keywords: Agriculture - economic aspect